Graft‐Versus‐Host Disease After Simultaneous Pancreas–Kidney Transplantation: A Case Report and Review of the Literature. Issue 11 (12th September 2014) - Rossi, A. P.; Bone, B. A.; Edwards, A. R.; Parker, M. K.; Delos Santos, R. B.; Hagopian, J.; Lockwood, C.; Musiek, A.; Klein, C. L.; Brennan, D. C.
<x xml:space="preserve">Abstract</x> Graft‐versus‐host disease (GVHD) after solid organ transplantation is rare and usually fatal. We present, to our knowledge, the second successfully treated case in a simultaneous pancreas–kidney (SPK) transplant recipient. A 29‐year‐old female with end‐stage renal disease from type 1 diabetes mellitus received an SPK transplant from a male donor, with rabbit‐antithymocyte globulin induction. Twelve days posttransplant, she was readmitted with abdominal pain, nausea and vomiting. She developed leukopenia, abnormal liver enzymes, fever and a skin rash. Skin biopsy showed interface dermatitis consistent with allergic reaction versus GVHD. Fluorescence in situ hybridization of the skin biopsy showed 28% of cells had a Y chromosome confirming GVHD. Short tandem repeats (STR) enriched for CD3+ cells from peripheral blood showed a mixed chimerism. She was successfully treated with a single plasmapheresis to remove antithymocyte globulin, high‐dose steroids, photopheresis and high tacrolimus levels (12–15 ng/mL). Five months after transplantation, she has normal renal function and white blood cell count, normal hemoglobin A1C and no evidence of peripheral blood donor chimerism. In conclusion, early diagnosis of GVHD after SPK transplantation may allow successful treatment. STR enriched for CD3+ may be useful to evaluate the response to therapy.